2017
DOI: 10.1111/jocs.13148
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic versus open radial artery harvesting: A meta-analysis of randomized controlled and propensity matched studies

Abstract: ERAH reduces wound complications and does not affect graft patency, or short- and long-term mortality compared to ORAH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 21 publications
(25 reference statements)
1
19
0
Order By: Relevance
“…Shapira et al [35] showed that the cost of an endoscopic kit, including the disposable Harmonic shears, is $550. ERAH was also found to take a longer duration as compared to ORAH with an associated steep learning curve in inexperienced hands [36] . The reported learning curve for endoscopic harvest ranges from 5 to 30 cases [37] .…”
Section: Radial Artery Graft Harvest Could Be Performed Open or Endosmentioning
confidence: 96%
See 2 more Smart Citations
“…Shapira et al [35] showed that the cost of an endoscopic kit, including the disposable Harmonic shears, is $550. ERAH was also found to take a longer duration as compared to ORAH with an associated steep learning curve in inexperienced hands [36] . The reported learning curve for endoscopic harvest ranges from 5 to 30 cases [37] .…”
Section: Radial Artery Graft Harvest Could Be Performed Open or Endosmentioning
confidence: 96%
“…Finally, a recent meta-analysis of randomized controlled and propensity matched studies comparing the endoscopic approach of harvesting the RA graft with the open approach demonstrated a lower incidence of wound complications [odds ratio (OR) = 0.33, 95% CI: 0.14-0.77, P = 0.01] with similar patency rates and early mortality rates (OR = 1.32, 95% CI: 0.76-2.27, P = 0.32 and OR = 0.78, 95% CI: 0.10-6.11, P = 0.81) [ Figure 2] [57] .…”
Section: Comparison Of Outcomes Between Erah and Orahmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to its improved long‐term patency over saphenous vein grafts and its easy accessibility, the radial artery has become the second most common arterial conduit used in coronary artery bypass graft (CABG) surgery. It can be harvested by either open or endoscopic techniques with minimal trauma, and can be used as a free or composite graft . Its patency, however, may be reduced when the distal target vessel has a <80% stenosis.…”
mentioning
confidence: 99%
“…It can be harvested by either open or endoscopic techniques with minimal trauma, and can be used as a free or composite graft. 1 Its patency, however, may be reduced when the distal target vessel has a <80% stenosis. Concerns have also been raised when the radial artery is harvested from patients with longstanding diabetes mellitus and poor glycemic control, as these patients have been shown to have developed intimal changes in their radial arteries when they are examined under electron microscopy.…”
mentioning
confidence: 99%